Dynamics of Syiqaq and Divorce in Border Regions: A Socio-Legal Analysis at the Nunukan Religious Court - Asiah, Nur; Muhibbin, Moh; Masruchah, Siti (Journal of Law, Politic and Humanities, 2025)
National border regions constitute liminal spaces where social norms and morality are contested. This article analyzes the dynamics of syiqaq (persistent marital disputes) and divorce in Nunukan Regency, North Kalimantan, a border area experiencing the erosion of family resilience due to digital transformation. This study aims to explore the shifting causality of divorce, judicial discretion in interpreting syiqaq, and the effectiveness of mediation. Employing a qualitative socio-legal approach within a post-positivist paradigm, the study integrates analysis of court verdicts from 2022-2024 with in-depth interviews with judges, mediators, and litigants. Data were analyzed using the Miles and Huberman interactive model with source triangulation. Findings reveal a fundamental shift in divorce causality from economic factors toward the dominance of a digital morality crisis, particularly online gambling and social media-facilitated infidelity. Judges exercised progressive ijtihad by expanding the interpretation of syiqaq to accommodate new social pathologies, validated through SEMA No. 3 of 2023. However, mediation proved systemically ineffective in morally driven cases due to formalistic approaches that fail to address psychological trauma. It is concluded that family resilience in border areas requires a comprehensive revitalization of social ethics beyond formal legal intervention.